InGenius : a crash course on creativity - Seelig, Tina Lynn (HarperOne, 2012)
"In inGenius, Seelig reminds us that creativity is not just something that you think about - it is something that you do. It is as natural as breathing, and just as necessary for leading a successful and fulfilling life. Creative solutions are required because the status quo is never good enough, and our goal should always be to push beyond the limits of what seems possible. Great ideas are needed to solve all the problems we face and to enrich our lives."--